Alveolar wound healing alteration under uranyl nitrate intoxication - Guglielmotti, M. B.; Ubios, Angela M.; Cabrini, Rómulo Luis (John Wiley & Sons, Inc., 1985)
Fil: Guglielmotti, M. B. Comisión Nacional de Energía Atómica; Argentina